1996
DOI: 10.1364/ao.35.006210
|View full text |Cite
|
Sign up to set email alerts
|

Cross-shaped bandpass filters for the near- and mid-infrared wavelength regions

Abstract: A photolithographic process has been used to form cross-shaped patterns in 3-μm-thick nickel foils. Patterns with cross arm dimensions in the 10-20-μm range, and with periodicities in the 16-26-μm range, yield self-resonant bandpass filters for wavelengths in the 20-25-μm region. Transmittances as high as 80% were achieved with center wavelength-to-bandwidth ratios (λ(R)/Δλ) of ~5. We present a simple empirical formula that relates the wavelength of peak transmittance, or resonant frequency, with cross dimensi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
10
0
4

Year Published

2008
2008
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 32 publications
(15 citation statements)
references
References 5 publications
1
10
0
4
Order By: Relevance
“…For a 0.3 mm thick mesh filter resonant at 300 GHz, the length is found to be 0.527 mm by full-wave simulations [19]. This is in good agreement with the calculated value of 0.531 mm from the empirical formula derived by Möller et al [20].…”
supporting
confidence: 83%
“…For a 0.3 mm thick mesh filter resonant at 300 GHz, the length is found to be 0.527 mm by full-wave simulations [19]. This is in good agreement with the calculated value of 0.531 mm from the empirical formula derived by Möller et al [20].…”
supporting
confidence: 83%
“…The filter central frequencies transmission and respective bandwidths were compared with results obtained by other authors [4,11,12], as shown in Figs. 6 and 7, respectively.…”
Section: Discussionmentioning
confidence: 98%
“…18 The use of the Bragg stacks as an interference filter between the blackbody emitter and PV cell to tailor emission also leads to peaks in the emission spectrum outside the desired bandpass region. 19 Chase and Joseph 20 and Moller et al 21 first proposed using a crossmesh array in thin metallic films as a bandpass filter for the infrared region and found that the wavelength peak reflection is determined by the dimensions of the cross. Further contributions by Morgan et al reported the design and fabrication of nanoscale cross-patterned optical filters.…”
Section: Introductionmentioning
confidence: 99%